Ocean Tourism and Poverty Alleviation in India: An Analysis - Godara, Rajender S.; Haider, Ahsanuddin; Jafri, Samreen (The journal of contemporary issues in business and government, 2021)
Blue tourism is important for sustainable development and become one of the largest industries to generate income and promote economic growth and development. Blue tourism is a high- income, healthy and clean industry for the country which has borders with the sea and free water. The growth of blue tourism contributes to poverty alleviation and its prosperity reflects the political, economic, social, security, cultural, and scientific stability of the countries of the world. Tourism has a profound effect on the economic situation of some developed and underdeveloped countries in recent years, making it one of the largest economic sectors in many countries today with the potential to impact poverty reduction. The study used the Ordinary Least Squares (OLS method), which attempted to share the impact of ocean tourism on poverty in India during the time series period (2001-2019. The findings prove Ocean Tourism and Poverty have a positive relationship.